2012
DOI: 10.1111/j.1750-3841.2012.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam Baking on Acrylamide Formation and Browning Kinetics of Cookies

Abstract: The kinetics of acrylamide formation and browning of cookies will possibly allow definition of optimum baking temperatures and times at convectional and steam-assisted baking ovens. The kinetic model can be used by developing baking programs that can automatically control especially a new home-scale steam-assisted hybrid oven producing healthy products, for the use of domestic consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…As can be observed, BI indicated first-order kinetics, as also shown by other authors [31][32][33]. BI increased with heating time, showing higher values for higher lactose content.…”
Section: Maillard Reaction Kineticssupporting
confidence: 78%
“…As can be observed, BI indicated first-order kinetics, as also shown by other authors [31][32][33]. BI increased with heating time, showing higher values for higher lactose content.…”
Section: Maillard Reaction Kineticssupporting
confidence: 78%
“…The highest value of BI was noticed for biscuits prepared from buckwheat fl our fermented by L. plantarum IB and the lowest one for the control sample (27.7 and 21.8, respectively). The browning index could be used to quantify the color change attributed to caramelization and Maillard reactions [Isleroglu et al, 2012]. The cited authors found a positive correlation between the browning index and acrylamide formation in cookies baked in different types of oven and at different temperatures.…”
Section: Resultsmentioning
confidence: 95%
“…Its reaction mechanism and degradation pathways have been illustrated by using multiresponse kinetic modelling (Martins and others ; Martins and Van Boekel ). In addition, acrylamide is known as an intermediate product rather than an end product in the Maillard reaction, the kinetics of acrylamide formation has also been investigated frequently via multiresponse kinetic modelling (Claeys and others ; Knol and others ; De Vleeschouwer and others ; Isleroglu and others ). Admittedly, the changes in N‐(1‐deoxy‐ d ‐fructos‐1‐yl)‐glycine and acrylamide formation can be predicted by multiresponse kinetic modelling and explained by the corresponding proposed reaction network.…”
Section: Introductionmentioning
confidence: 99%